Selection Indicators of Yield Components and Yield for Improvement of Local Sweet Potato under Water Stress - Helen Hetharie; Simon Hadi Teguh Raharjo; Edizon Jambormias; Reny Tomasoa; Anna Yuliana Wattimena (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Genetic diversity is required for crop improvement against environmental stress. Astudy wasconducted to determine characters as selection indicators of water-stress tolerance, and of yield components and yield. The research method involved a one-factor experiment with 21 sweet potato clones, using a Completely Randomized Block design with three replicates. Water stress in this study mean that the bottom of plants was submerged in water at 2 and 3 months of age. Determination of selection indicators was conducted by estimating the coefficients of genetic and phenotypic variations, heritabilities, genetic advance and correlation test result. The characters of number of leaves, individual leaf area, leaf area per plant, leaf area index, stem length, internode length, number of tubers (storage root), individual tuber weight and yieldas selection indicators of water stress tolerance. Selection indicators of yield components consisted of less number of leaves, small leaf size, short stemsand number of branches, whereas selection indicators of yield were small leaf size, number of branches, number of tubers and individual tuber weight. Selection became effective and efficient when the selection indicators were influenced greatly by genetic factors.